PENATALAKSANAAN GIZI PADA KANKER BERBASIS GENETIK (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Cancer, also known as Neoplasia, is a 'new growth' that occurs when cells in a tissue or organ develop uncontrollably as normal growth should. In malignant neoplasia, cells can develop and spread to the surrounding tissues directly or to other organs that are located far apart through the blood vessels or spleen, resulting in the spread of malignant cells or metastases. The exact cause of neoplasia is still difficult to prove. Several studies have shown that there is a close relationship between nutrition and cancer. Based on its association with cancer, nutrition is divided into three characteristics, namely Causing Cancer, Promoting Cancer, and Protecting Cancer.Malnutrition is a major problem in cancer patients. Cancer cachexia is a complex syndrome characterized by anorexia, weight loss, skeletal muscle atrophy, immune system dysfunction and various immune system alterations. Food intake can be influenced by several factors such as appetite, swallowing ability and absorption in the body. In cancer, there are changes in the metabolism of carbohydrates, proteins, and fats in the body. Hypermetabolism of these nutrients occurs due to the presence of cancer cells which causes an increase in the need for glucose as an energy source which can also result in protein turn-over and increased lipolysis. Administration of radiation or chemical therapy can also affect food intake. Radiation therapy has side effects such as decreased appetite, nausea, vomiting, stomatitis, dry throat, and difficulty swallowing. The side effects that occur in the digestive tract result in a decrease in food intake and an impact on decreased nutritional status.The need for energy and macronutrients (protein, fat, and carbohydrates) in cancer patients is different for each individual. This need can be influenced by several situations and conditions that occur in the body of a cancer patient, starting from the level of stress, the level of metabolism that occurs in the body, as well as conditions of complications of diseases other than cancer. Adequate fulfillment of nutritional needs is expected to improve malnutrition that occurs. Nutritional support given according to the circumstances and individual needs of the patient in terms of amount, composition and method of administration should be done early.